THE RATIONAL ACTION OF ELITE: MITIGATION THE COVID-19 AND COMMUNITY RESISTANCE IN PESANTREN SALAFIYAH SYAFI’IYAH SITUBONDO - Nurul Azizah (Balai Penelitian dan Pengembangan Agama Semarang, 2022)
The role of religious elite has legitimation as the highest symbolic representation of religious authorities in society especially on Islamic boarding school area. In this digital era where the public space widely open, there is a tendency related to the transformation of religion thinking paradigm, culture and tradition which is becoming interesting discussion. As result, there is a trend of dualism that is accommodative and resistance society. In different interpretation context, religion is no longer elitist, absolute, and contestation. This paper aims at analysing the society resistance and the role of religion elite to anticipate the spread of Covid-19 in Islamic boarding school. Based on the result of interview, observation, and data analysis of descriptive qualitative research, it revealed: First, there is community anachronism paradigm to religion and culture, emergence of society resistance to rules which have been determined by the government. Second, the role of religion elite and religion fatwa has been succeeded to apply in Islamic boarding school area and people who have patron and client relationship. The spreading of information is very effective through social media. Third, the government policy related to the restriction of community activities and socialization of religion elite fatwa are not quite effective to decrease the society resistance. This paper suggested it is necessary to have synergy between religion elite and government, so that it can increase the community rationality to the religion and culture understanding and it is not stuck on orthodox thinking in this Covid -19 pandemic.